Substance use disorders: diagnosis and management for hospitalists - Ahmed K. Pasha; Arnab Chowdhury; Sanah Sadiq; Jeremiah Fairbanks; Shirshendu Sinha (Greater Baltimore Medical Center, 2020)
Substance use disorder is a significant health concern. Hospitalists manage patient with various forms of substance use disorder on a daily basis. In this review, we have tried to synthesize evidence together to give a brief, yet succinct, review of commonly encounters disorders; alcohol intoxication and withdrawal, opioid intoxication and withdrawal, cocaine intoxication and methamphetamine intoxication. We describe clinical features, diagnosis and management, which would serve as a great resource for hospitalist when managing these complicated patients.